1992
DOI: 10.1002/ijc.2910520319
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids, non‐phorbol‐ester‐type tumor promoters, stimulate the phosphorylation of protein kinase C substrates in human platelets and colon cell line HT29

Abstract: Protein kinase C (PKC) is the target for a number of tumor promoters. The mechanism underlying the promoting effects of bile acids in colorectal cancer is not understood. We report that sodium deoxycholate (DOC) triggered activation of PKC in physiological conditions. The biphasic effects of DOC upon PKC activation were Ca(2+)-stimulated and did not require phosphatidylserine (PtdSer) as phospholipid co-factor. The optimal rate of activation was obtained at 0.4 mM DOC and reached approximately half the maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 14 publications
4
55
0
Order By: Relevance
“…While bile acids are not mutagenic, they have been shown to act as tumour promoters in animal studies (Narisawa et al, 1974;Mahmoud et al, 1999) and PKC has been identified as their molecular target (Pongracz et al, 1995). We confirm here that the secondary bile acid UDCA was able to activate PKC in whole cells (Huang et al, 1992) and show that this action was restricted to the classical PKC isoenzyme PKC-a. Although UDCA was the focus of this study, we have also shown that other bile acids can inhibit butyrate-induced apoptosis, including CDCA (McMillan et al, 2000), and this bile acid also activates PKC-a (data not shown).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…While bile acids are not mutagenic, they have been shown to act as tumour promoters in animal studies (Narisawa et al, 1974;Mahmoud et al, 1999) and PKC has been identified as their molecular target (Pongracz et al, 1995). We confirm here that the secondary bile acid UDCA was able to activate PKC in whole cells (Huang et al, 1992) and show that this action was restricted to the classical PKC isoenzyme PKC-a. Although UDCA was the focus of this study, we have also shown that other bile acids can inhibit butyrate-induced apoptosis, including CDCA (McMillan et al, 2000), and this bile acid also activates PKC-a (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…The tumour-promoting effects of bile acids have been ascribed predominantly to their potent activation of protein kinase C (PKC) (Huang et al, 1992). PKC is a family of 11 isoenzymes that are differentially regulated and play specific roles in the control of cell proliferation, differentiation and apoptosis (Clemens and Trayner, 1992;Deacon et al, 1997).…”
mentioning
confidence: 99%
“…The protein-DNA complex that formed was separated on a 4% polyacrylamide gel as described under "Experimental Procedures." cholic acid or conjugated bile acids (32). The present data therefore suggest a plausible mechanism to explain the promotion of esophageal (42)(43)(44) and colon (24 -27) cancer by bile acids: induction of COX-2.…”
Section: Discussionmentioning
confidence: 51%
“…Bile acids are known tumor promoters that activate PKC, which may be the mechanism of bile acid-induced carcinogenesis (31)(32)(33). Dihydroxy bile acids are more effective in activating PKC than mono-and trihydroxy bile acids (32).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the ability of secondary bile acids to act as tumor promoters by stimulating signal transduction and cancer-promoting genes. Activation of protein kinase C, which is a common event triggered by many tumor promoters, was reported in cultured colon cells that were exposed to deoxycholic acid [12]. Additionally, activation of the transcription factors, AP-1 [13] and NF-κB [14], as well as the NF-κB -responsive cyclooxygenase-2 (COX-2) gene [15], has been reported.…”
Section: Introductionmentioning
confidence: 98%